Therapeutic Effects of Yoga on Varicose Veins: A Comprehensive Clinical Study - Sharma, Sunil; Sharma, Rajit; Verma, Ambika (International Research Journal of Ayurveda & Yoga, 2025)
Background: Varicose veins, a common venous disorder, result from venous valve incompetence, leading to blood pooling and vein dilation. Conventional treatments such as compression therapy, sclerotherapy, and surgical interventions focus on symptom management rather than addressing underlying causes. Holistic approaches such as Yoga and Ayurveda offer promising complementary strategies by improving circulation, reducing venous stasis, and promoting vascular health. Aim: This study aimed to evaluate the therapeutic effects of a structured Yogic regimen on primary varicose veins among female subjects, assessing changes in venous function, symptom severity, and overall vascular health. Materials and Methods: A total of 35 female participants diagnosed with primary varicose veins from Nurpur, Kangra, Himachal Pradesh, were selected through purposive sampling. Participants underwent Doppler ultrasound testing for initial diagnosis. Aquasi-experimental pre-test and post-test design was employed, with assessments based on the revised venous clinical severity score (VCSS). Ethical approval was obtained from the Chandigarh Yoga Institutional Ethical Committee. Intervention: The intervention consisted of a structured 12-week Yogic regimen, including Asanas (Tadasana, Trikonasana, Viparita Karani, and others), Pranayama (Ujjayi, Nadi Shodhana, Bhastrika, and Bhramari), and Relaxation (Shavasana). Sessions were conducted 6 days a week for 60 min, focusing on improving circulation, reducing venous congestion, and strengthening lower limb muscles. Dietary and lifestyle modifications, such as increased fiber intake, hydration, and avoiding prolonged standing, were also incorporated. Results: The mean VCSS score significantly decreased from 7.67 (pre-test) to 1.94 (post-test), indicating substantial improvement in varicose vein symptoms. The standard deviation reduced from 1.902 to 0.617, reflecting uniform improvement among participants. A paired t-test analysis yielded a t = 16.9532 (P < 0.05), confirming the statistical significance of the intervention. Participants reported reduced pain, swelling, and discomfort, demonstrating the effectiveness of the Yogic regimen in alleviating varicose vein symptoms. Conclusion: The findings suggest that Yoga serves as an effective non-pharmacological intervention for managing primary varicose veins. Significant improvements in venous function and symptom relief highlight Yoga’s potential in vascular health management. Further studies with larger sample sizes and comparative analysis with conventional treatments are recommended to validate these findings.